OPTIMIZATION OF DA'WAH COMMUNICATION OF LAZISMU MAKASSAR IN INCREASING MUZAKKI PARTICIPATION: OPTIMALISASI KOMUNIKASI DAKWAH LAZISMU MAKASSAR DALAM MENINGKATKAN PARTISIPASI MUZAKKI - Muhammad Suhufi; Mahmuddin; St. Aisyah BM (SOSIOEDUKASI, 2026)
This study aims to analyze the optimization of da'wah communication carried out by Lazismu Makassar in an effort to increase muzakki participation and loyalty. Through a descriptive qualitative approach, this study identifies forms of communication (da'wah bi al-lisan, bi al-qalam, and bi al-hal), media strategies (offline and digital), as well as supporting and inhibiting factors that affect the effectiveness of philanthropic da'wah. The findings show that the integration of persuasive, humanist, and transparent approaches, combined with the use of digital media such as WhatsApp, Instagram, Facebook, and TikTok, successfully builds emotional closeness and public trust. Personal communication through WhatsApp has proven to be the most effective channel in maintaining muzakki loyalty. The main supporting factors include the support of the Muhammadiyah network, a structured management system, real empowerment programs, and adaptive digital literacy. On the other hand, the low public understanding of zakat obligations and the preference for direct distribution to mustahik are still structural obstacles. This research enriches the treasures of contemporary da'wah communication theory by integrating the perspective of relationship marketing, social identity theory, and the principles of da'wah bil hikmah. The practical implications emphasize the need to strengthen zakat literacy, optimize social impact-based storytelling, and standardize measurable digital communication to strengthen the sustainability of Islamic philanthropy in the urban era.